Teaching philosophies revalued: beyond personal development to academic and institutional capacity building - Ruge, Gesa; Schӧnwetter, D.J.; McCormack, C.; Kennelly, R. (2023)
This research investigates the value of teaching philosophies (TP) for today’s academics and their institutions. It offers a new framework to enhance academic development, personal resilience, and institutional capacity building. Since the 1990s, TPs have been formalised as personally constructed and reflectively written statements of educational values, beliefs, and practices. Whereas within universities, TPs have been institutionalised for academic performance reviews, awards, and promotions. In-depth personal interviews on TPs and their value on personal journeys and institutional experiences were conducted with academics from Australia and Canada. The findings highlight the value and future potential of TPs beyond a formulaic role.